Material capacity planner (MCP): a semiconductor fabrication case study - Loi, Kok Ming (2008)
This dissertation analyses the mechanics of a supply chain-planning tool, Material Capacity Planner (MCP) for the complex business and production planning process of Chartered Semiconductor Manufacturing. This dissertation also discusses the model approach, various considerations, conditions, and system integration requirements for the MCP implementation.